Dynamics of surface water and groundwater quality using water quality indices and GIS in river Tamsa (Tons), Jalalpur, India - Ghazala Siraj; Haris Hasan Khan; Arina Khan (HydroResearch, 2023)
Water samples were collected along the Tamsa river and adjacent groundwater in 2019 and 2020, and analyzed for pHh, temperature, TDS, EC, TH, major ions, and trace elements. Statistical and spatial analysis and geochemical plotting were used. Results show that both river water and groundwater are hard and slightly alkaline. Groundwater has higher concentrations of major ions and silica than river water. River water is more alkaline than groundwater. The main hydrogeochemical facies is the Ca + Mg-HCO3 type. Mg + 2, HCO3, Ni, WAWQI, TH, and MH exceed the permissible limits in both river and groundwater at a few locations, and TDS, Ca + 2, Cl-, F-, Mg/Ca, RSC, KR, PS, CR also exceed in groundwater at few locations. Water is suitable for most locations for drinking, domestic, and irrigation purposes. Rock weathering dominance, cation-anion exchange, and anthropogenic activities are found to influence water chemistry in the region.